Tourism and Regional Studies in Galicia in the Late XIX and First Half of the XX Century - Vasyl Lutskyi; Bogdan Mytskan (Lesya Ukrainka Volyn National University, 2018)
The purpose of the article is to highlight the general conditions and main directions of development of tourism and regional studies in Galicia in the late XIX and first half of the XX century. Author analyzes the role and contribution of individual scholars and public figures in the development of the tourist-local lore movement, starting with the activities of the members of the «Ruska trijcia». It was established that their travels were ethnographers and directed to study ethnographic and linguistic features of the region. Due to the work of I. Havryshkevich, O. Partytsky, cartography was developed, the tourist routes for the first time in the vicinity of Galicia and Lviv were described. In the course of regional travels A. Petrushevich and I. Sharanevych created the first Ukrainian museums in Lviv, an ethnographic exhibition was held in Ternopil, and since 1882 have begun excavations of the city of Galich. An important role in the development of tourism and local lore studies was played by I. Franko and V. Shukhevych. Author pays special attention to the activities of tourist associations «Chornogora» in Stanislaviv, «Plai» in Lviv and in Ternopil. Already in the 20's of the XX century tourist studies of children and youth became an integral part of the activity of the societies «Sich», «Sokil», «Lug», «Orly» and Plast. Metropolitan Andrey Sheptytsky and historian I. Krypiakevich took an active part in popularizing and developing the tourist-local lore movement. Author asserts that the development of the tourist-local lore movement in Galicia contributed to the growth of the national consciousness of children and youth.